Newnes C++ pocket book - Sexton, Conor (Newnes, 1996)
This is the second edition of The C++ Pocket Book, first published in 1993, and reprinted in 1995. To the author's knowledge, no book is yet available that addresses as a whole the C++ language as defined by the ANSI Draft Standard. This second edition is an attempt to fit in a slim volume the essential facilities of ANSI C++. This book presents the essential subset of the ANSI Draft Standard C++ language and environment. Every facility of the language is addressed, while the component parts of the new C++ Library are summarised. New language facilities, for example runtime type identification (RTTI) and namespaces, are included. The coverage of templates and exception handling is updated, as is that of many other aspects of the language. There is an improved exposition of such topics as memberwise initialisation and assignment; multiple inheritance and virtual base classes; and the internal implementation of virtual functions.